Understanding halal cosmetic purchase intention: A systematic literature review - Hidayah, Risa Nur; Lestari, Puput (Halal Studies and Society, 2025)
Halal cosmetic industry is widely recognized as a significant global beauty and personal care market segment. Alongside the rapid growth, understanding consumer purchase intention toward products has become a key focus of academic investigations. Therefore, this systematic literature review aims to identify the key determinants of purchase intention and uncover prevailing trends in the context of halal cosmetic. Using the PRISMA principles, a total of 15 relevant studies were collected from the Scopus database. The results showed that purchase intention towards halal cosmetic products was influenced by various key determinants reflecting the interaction between internal and external factors. The most mentioned variables across various studies include religiosity, halal awareness, attitudes towards products, subjective norms, perceived behavioral control, as well as emotional and social values. In addition, external factors such as influencer impact, trust in halal logos, and digital marketing strategies also play a significant role in shaping purchase intention, both among Muslim and non-Muslim consumers. Based on the results, purchase intention towards halal cosmetic products cannot be explained in a single dimension, but rather from a complex dynamic between personal, psychological, social values, and exposure to marketing information. This literature not only identifies the main determinants of purchase intention for halal cosmetic products but also shows the evolving direction of investigation that is increasingly complex, interdisciplinary, and contextual, in line with the changing behaviors and expectations of modern Muslim consumers.